Análisis de los actores claves involucrados en la gestión turística del Cantón Urdaneta - Suque Mora, Evelyn Paola (2022)
This case study aims to analyze the key actors involved in the tourism management of the Urdaneta Canton and their main functions that they perform within the public and private sectors, its objective is to make known how their work influences the development of tourism projects in the Canton. The type of research used is qualitative because an interview will be conducted with the Director of the Department of Tourism, it is a documentary research with which information is obtained from the different actors who have studied the functions of the actors of tourism management is descriptive by that describes all the phenomena and all the situations that are generated around the tourist management that it has in relation to the functions of the main actors and as well as the projects that have been carried out during the management of these authors in the Urdaneta Canton. In this investigation, the following have been revealed: in municipal management it is probably one of the most novel and promising dimensions and competencies of the currently valid approach to local development, which in such a way in the summer seasons are the ones with the greatest tourist influx. In the canton where its patron saint and cantonal festivities are celebrated, public events are held, as well as regattas are held in order to generate economic reactivation.